Towards an Educationally Meaningful Curriculum: Epistemic Holism and Knowledge Integration Revisited - Carr, David (British Journal of Educational Studies, 2007)
ABSTRACT: Despite the ‘progressive’ influence of the English Plowden Report and Scottish Primary Memorandum on British primary curricula from the 1960s onwards, secondary education has generally continued to follow a more traditional subject-centred route and post-war educational theorists have not generally been favourably inclined to other than subject-based modes of curriculum planning and organisation. However, in the light of current curriculum reviews on both sides of the Scottish border – calling for more educationally meaningful curricula – the perennial issue of how school knowledge might best be ordered for the coherent educational experience of pupils seems worth revisiting. To this end, this paper examines some of the influential post-war philosophical arguments against integrated and interdisciplinary approaches to the curricular organisation of knowledge, concluding that they are not as compelling as they might formerly have seemed.